2016
DOI: 10.4102/ajlm.v5i3.508
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Ebola virus disease laboratory system and related challenges in Liberia

Abstract: Prior to the Ebola virus disease outbreak in Liberia, the laboratory system was duplicative, fragmented and minimally coordinated. The National Reference Laboratory was conceptualised to address the existing challenges by promoting the implementation of effective and sustainable laboratory services in Liberia. However, in a resource-limited environment such as Liberia, progress regarding the rebuilding of the health system can be relatively slow, while efforts to sustain the transient gains remain a key challe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 3 publications
1
14
0
Order By: Relevance
“…Other challenges experienced during the implementation of drug resistance testing included frequent electricity disconnections, which was solved by installing a backup generator to ensure a constant supply of power. This corroborates other previous studies that highlighted similar findings in resource limited settings ( Kennedy et al , 2016 ; Nkengasong et al , 2018 ). Furthermore, supply chain insufficiency, which delayed timely delivery of reagents, consumables, and laboratory equipment, was a major setback in implementing HIVDR testing.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Other challenges experienced during the implementation of drug resistance testing included frequent electricity disconnections, which was solved by installing a backup generator to ensure a constant supply of power. This corroborates other previous studies that highlighted similar findings in resource limited settings ( Kennedy et al , 2016 ; Nkengasong et al , 2018 ). Furthermore, supply chain insufficiency, which delayed timely delivery of reagents, consumables, and laboratory equipment, was a major setback in implementing HIVDR testing.…”
Section: Discussionsupporting
confidence: 93%
“…There are a few laboratory specialists equipped with these skills, making them highly sought after in the job market. This is a challenge in a low resource set up as training personnel on this area is quite expensive ( Abimiku, 2009 ; Kennedy et al , 2016 ; Nkengasong et al , 2018 ; WHO, 2010 ). To counteract this challenge, one of the staff won a training grant to learn HIVDR testing from a laboratory that was already established.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 The surveillance systems were weak and fragmented by specific disease programs in a way that impeded their flexibility to adapt to and detect other emerging and infectious diseases that fell outside of their specified mandates. 23 In contrast, the polio surveillance system in Nigeria has developed to serve other notifiable conditions with its strong disease detection, laboratory networks, immunization services, and outbreak preparedness and response structures. 24 In doing so, Nigeria has demonstrated that cross-cutting capabilities in the polio surveillance system could help in other disease outbreaks, while still serving polio-specific needs.…”
Section: Within the Health Sectormentioning
confidence: 99%
“…The laboratory testing service was limited to hospitals, health centers and clinics. There was no specialized and molecular testing capacity at the national reference laboratory which was providing limited testing services for epidemic-prone diseases such as measles, rubella and yellow fever [2,3].…”
Section: Introductionmentioning
confidence: 99%